Sustainable building design. Principles and practice. - (:unkn) unknown (Wiley Blackwell, 2018)
The book offers detailed, environmentally sound design solutions to a wide range of building engineering challenges. The text uses case examples and project data provided by engineers and designers at Arup Associates. Whilst the book stresses the importance of a unified approach to design, the text is divided into six principal chapters, each addressing an important aspect of sustainable architecture and engineering. These chapters (Master Planning, Transport, Energy, The Building Envelope, Environmental Services, and Materials) may be read on their own or in sequence as part of a narrative. Throughout the book, photographs, architectural and engineering drawings and diagrams, examples, and other data illustrate the case studies. Numerous web links are provided to additional information. The book focuses on the work of Arup Associates, the award winning architectural and engineering practice, uses real-life examples of functioning buildings and structures to provide information and guidance on the development of sustainable solutions.
Keywords: Bebauung; Stadtökologie; Architektur; Gebäude; Energie; Baumaterial; Bautechnik; Verkehr; Ökologisches Bauen; Nachhaltiges Bauen; Nachhaltigkeit; Gebäudehülle; Klimaschutz